Uwarunkowania prawne funkcjonowania systemu informatycznego rachunkowości - Szymczyk-Madej, Katarzyna (Legal Framework of Functioning of Accounting Information Systems, 2005)
Development of information technology (IT) and data storing devices as well as availability of Accounting Information Systems (AISs) on the Polish market have led not only to common utilization of IT in the field of book-keeping, but also to substantial changes in keeping and archiving books. Variety of software packages, which are developed by applying the latest IT achievements, causes that AISs, which are utilized by business entities, function based upon various solutions. However, the basic criterion of deploying a given AISs is its compliance with accounting law and principles. Non--compliance with legal requirements disqualifies the software as the non-standard IT tool. The Accounting Act of September 29th, 1994 regulates the aspects related to applying IT systems in accounting. The present article analyzes this topic.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 349-361